Potential neuroprotective effects of a grape seed-derived polyphenol extract via modulation of redox signaling in the context of ischaemic stroke - Mfisa, Kabelo (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.